2017
DOI: 10.1002/smll.201701607
|View full text |Cite
|
Sign up to set email alerts
|

Facet Engineered Interface Design of Plasmonic Metal and Cocatalyst on BiOCl Nanoplates for Enhanced Visible Photocatalytic Oxygen Evolution

Abstract: Integration of plasmonic metal and cocatalyst with semiconductor is a promising approach to simultaneously optimize the generation, transfer, and consumption of photoinduced charge carriers for high-performance photocatalysis. The photocatalytic activities of the designed hybrid structures are greatly determined by the efficiencies of charge transfer across the interfaces between different components. In this paper, interface design of Ag-BiOCl-PdO hybrid photocatalysts is demonstrated based on the choice of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Therefore, the results of the photocurrent responses and PL studies demonstrate that the heterostructure between BiOCl and BiOBr can effectively suppress the recombination of the photogenerated electrons and holes, and thus enhance the corresponding photocatalytic reduction of aqueous Cr(VI). 19,36,37 The recombination and separation of the photogenerated electrons and holes could be further investigated by timeresolved transient PL (TRPL), as shown in Fig. 4b.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Therefore, the results of the photocurrent responses and PL studies demonstrate that the heterostructure between BiOCl and BiOBr can effectively suppress the recombination of the photogenerated electrons and holes, and thus enhance the corresponding photocatalytic reduction of aqueous Cr(VI). 19,36,37 The recombination and separation of the photogenerated electrons and holes could be further investigated by timeresolved transient PL (TRPL), as shown in Fig. 4b.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…However, there are still some bottlenecks hindering its practical application, such as wide band gap and fast recombination of electron–hole pairs of single BiOCl 7 . Some efforts have been devoted to deal with those drawbacks, such as controlling exposed crystal facets 8 , varying morphology and size 9 , 10 , noble metal doping 11 , 12 , and constructing heterostructures 13 15 , etc. Among these methods, the fabrication of heterostructure is one of the most effective ways.…”
Section: Introductionmentioning
confidence: 99%
“…c) Deposition of noble metals; [21][22][23] Noble metal nanoparticlesl oaded onto the surface of the photocatalyst can cause as urface plasmon resonance (SPR) property and stronga bsorption of visible light, improving the interface charget ransfer to effectively enhance the photocatalytic activity. [23,24] d) Facet-controlled fabrication; [25][26][27] It has been demonstrated that exposed {0 01}f acets could enhance the thermodynamic stabilitya nd photogenerated electron-hole pairs separation efficiency of BiOCl. [26] f) Solid solution of BiOCl x Br 1Àx , [28][29][30][31] BiOBr x I 1Àx , [32,33] andB iOCl x I 1Àx .…”
Section: Introductionmentioning
confidence: 99%
“…b) Ion doping; Ion doping is considered to be a promising strategy to improve the photocatalytic performance, which increases the transport of charge carriers by narrowing the band gap or forming an intermediate impurity level between the conduction band and the valence band. c) Deposition of noble metals; Noble metal nanoparticles loaded onto the surface of the photocatalyst can cause a surface plasmon resonance (SPR) property and strong absorption of visible light, improving the interface charge transfer to effectively enhance the photocatalytic activity . d) Facet‐controlled fabrication; It has been demonstrated that exposed {0 0 1} facets could enhance the thermodynamic stability and photogenerated electron‐hole pairs separation efficiency of BiOCl .…”
Section: Introductionmentioning
confidence: 99%